431 - Establishing a Canadian National ECHO Educational Program focused on Mental Health of Older Adults. (October 2021) - Conn, David; Sokoloff, Lisa; Checkland, Claire; Guraya, Jasmeen; Ewa, Vivian; Feldman, Sid; Grief, Cindy; Navena Lingum, Andrea Hunter; MacKay, Ian; Rabheru, Kiran; Santiago, Anna; Seitz, Dallas; et al.
Abstract : Background: Project ECHO is a virtual, case-based capacity-building education program for healthcare providers. It was developed in New Mexico, USA but, due to its effectiveness, the model has now spread to 40 countries around the globe. Baycrest, the Canadian Coalition for Seniors' Mental Health and the Canadian Academy of Geriatric Psychiatry collaborated to launch a national ECHO for mental health and aging. This partnership, coordinated by a cross-Canadian Steering Group, allows for broad reach, including registration of learning partners from almost all Canadian provinces and territories. The program was funded by the RBC Foundation. Methods: ECHO COE: Mental Health pilot consisted of 2 cycles: 6 weekly sessions focused on broader mental health topics (e.g., delirium, mood disorders) 10 weeks with more specific topics (e.g., substance use disorders, sleep disorders) Needs assessments of healthcare providers and older adults informed the program curricula. Evaluation included weekly satisfaction surveys, and pre and post evaluations. Results: Participants: 154 healthcare providers participated in the 6-week session 39% of registrants were nurses or nurse practitioners, 35% allied health professionals, 14% physicians and 12% others 9 out of 10 provinces, 1 territory represented Preliminary findings (based on the first 6 sessions): High overall satisfaction (average of 4.5 out of 5). 99% would recommend the program to others 67% had already shared information with team members and colleagues. Conclusion: A national ECHO program is an effective way to bring together clinicians who work with and are interested in the mental health and wellbeing of older adults for education sessions, collaborative and mutual learning as well as for cross-jurisdictional knowledge transfer. Collaborative, cross-professional learning supports the exchange of best practice in mental health for older adults, supports the development of collegial national professional support and can address health system inequities. An international ECHO through IPA would be an exciting and valuable next step.